PARSEC PARAMETERIZATION METHODOLOGY FOR ENHANCING AIRFOILS GEOMETRY USING PSO ALGORITHM - da S. Neto, Rafael Alves; Noleto, Luciano Gonçalves; de Souza, Josiane do S. Aguiar; Brasil Jr., Antônio Cesar Pinho (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The electromechanical generating system is mainly based on the characteristics wherein the turbine has to ”harvest” the energy of a working fluid. Thus, the engineering behind the blades, such as the geometry and construction, must be effectively consolidated to increase the overall turbine efficiency. This work aims to go further into the computational principles of modeling the turbine blades, precisely, the hydrokinetic turbine hydrofoil built by LEA (Engineering Laboratory and Environment - UNB). The study has a focus on designing and analyzing, through numerical studies of parameterization and optimization profiles, blades using computational tools such as MATLAB R2016b and XFOIL. In this case, the model study is part of the airfoil theory combined with the Particle Swarm Optimization technic (PSO), which are implemented to get a maximum utilization of the aerodynamic coefficient CL over CD of the blade. Furthermore, an optimal turbine blade geometry, set by PARSEC parameter, is found and compared with results obtained from the original hydrofoil, using the software of profile analysis XFOIL, to certify the mathematical method, proving its effectiveness to parameterize hydrodynamic profiles and optimize their geometries. Keywords: Hydrokinetic Turbine. Airfoils. Parameterization and Optimization. Parsec. PSO.